2019
DOI: 10.3390/molecules24244466
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Zirconium Isomorphous Substitution into Zeolite Frameworks

Abstract: Systematic periodic density functional theory computations including dispersion correction (DFT-D) were carried out to determine the preferred location site of Zr atoms in sodalite (SOD) and CHA-type topology frameworks, including alumino-phosphate-34 (AlPO-34) and silico-alumino-phosphate-34 (SAPO-34), and to determine the relative stability and Brönsted acidity of Zr-substituted forms of SOD, AlPO-34, and SAPO-34. Mono and multiple Zr atom substitutions were considered. The Zr substitution causes obvious str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These suggested the relative effects of TiO 2 and ZrO 2 contents on the improvement of the water contents and IEC, respectively. Several studies have been reported on the Lewis acid and Brønsted acid sites of ZrO 2 -TiO 2 and other materials containing Zr or Ti atoms [ 16 , 19 , 20 ]. Lewis acid sites increase as the Ti content increases, whereas the Brønsted acid sites increase as the Zr content increases.…”
Section: Resultsmentioning
confidence: 99%
“…These suggested the relative effects of TiO 2 and ZrO 2 contents on the improvement of the water contents and IEC, respectively. Several studies have been reported on the Lewis acid and Brønsted acid sites of ZrO 2 -TiO 2 and other materials containing Zr or Ti atoms [ 16 , 19 , 20 ]. Lewis acid sites increase as the Ti content increases, whereas the Brønsted acid sites increase as the Zr content increases.…”
Section: Resultsmentioning
confidence: 99%
“…The mean square deviation parameters (Θ) can be used to represent the deformation of a local regular [MO 4 ] tetrahedron (Figure b) to reflect the local structural deformation of the T location normalΘ = 1 6 i = 1 6 false( α i α̅ false) 2 where α i represents the i th ∠O–M–O angle and α̅ is the average of six ∠O–M–O angles. In contrast to the commonly used local geometrical parameters, e.g., bond distances, it is found that the Θ parameter presents a correlation with the relative stabilities for different pure silica zeolite models.…”
Section: Methodsmentioning
confidence: 99%
“…Tetravalent metal ions (Ti 4+ , Ge 4+ , Zr 4+ , Sn 4+ ) can be incorporated into the zeolite by means of isomorphous substitution to introduce the well-defined Lewis acid center for the zeolite, which can enhance the catalytic activity of the zeolite for a designated reaction. Mal et al reported Sn-ZSM-12 zeolite with a Si/Sn >70 that could be used as an effective catalyst for the oxidation of phenol, m -cresol, and m -xylene, which performed better than the Sn-free ZSM-12. They also found that Sn-ZSM-12 exhibited better activity than mesoporous Sn-MFI/MEL in the oxidation of naphthalene and 2-methylnaphthalene to naphthol, 2-naphthalenemethanol and 2-naphthaldehyde .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Moreover, the different topologies of Lewis acid zeolites provide distinct confinement effects and shape selectivity. [27][28][29][30] Hence, Lewis acid zeolites may play an increasingly important role in developing new catalytic processes that convert raw resources into fuels and chemicals.…”
Section: Introductionmentioning
confidence: 99%